Managing process safety information based on process safety management requirements - Aziz, H.A. (2014)
Many accidents in process industries have occurred because of employees did not recognize the hazards and risk associated with the activities they were undertaking such as when operating, changing, or maintaining processes, plants, and equipment. Recognizing these hazards and risk requires a company to develop and maintain a corporate memory through an effective management of process safety information (PSI). One of the established standards that addressed the above issue is PSI of Process Safety Management (PSM) 29 CFR 1910.119(d). This article presents a PSI implementation technique that could fulfill with 29 CFR 1910.119(d) requirements. It provides organized strategies to manage documentations, communicate information, and written program for maintaining, revising, and updating hazardous chemical, equipment, and technology information. Process and Instrumentation Diagram (P&ID) is used as a foundation for data management. The developed technique has been transformed to computer database prototype known as Process Safety Information Management System (PSI4MS), which articulately demonstrate the concept. Implementation of this technique could help employers manage and control hazards of process plant and compliance with PSM regulation. Â© 2013 American Institute of Chemical Engineers.